Modeling and Design for a Sun Tracker Prototype Using Solar Cell and Arduino - Yuliadi Fajar Pangestu; Irfan Santiko (Universitas Amikom Purwokerto, 2023)
Solar cells are devices that can convert sunlight into electrical energy directly using photovoltaic technology. One of the factors that influences optimal absorption from solar cells is the installation of the solar cell surface. Installing the solar cell surface perpendicular to direct sunlight will maximize the energy produced. But in reality, most solar cell installations are still static or permanent with a fixed elevation angle so the solar cells cannot get the maximum intensity of sunlight because the sun always moves from east to west. Based on the existing problems, this prompted the author to create a prototype sun tracker to optimize solar cell absorption. This research uses experimental research methods with methods of data collection, observation, literature study, and system development from planning, needs analysis, design, testing, and results analysis. This system will work by directing the surface of the solar cell so that it is perpendicular to the direction of sunlight to Get maximum solar energy by using Arduino Uno as the main control which gets input values from the LDR sensor which is then processed and Arduino Uno will order the servo motor to move the solar cell towards the incoming sunlight. Monitoring this prototype work system uses a 16x2 LCD and also adds an IoT (Internet of Things) feature for monitoring the prototype work system remotely via smartphone.